Virtual reality psychological intervention helps reduce preoperative anxiety in patients undergoing carotid artery stenting: a single-blind randomized controlled trial - Liu, Yanhua; Wang, Rui; Zhang, Yang; Feng, Ling; Huang, Wenxia (Frontiers in Psychology, 2023)
Objective This study aimed to explore the effectiveness and applicability of a psychological intervention using virtual reality (VR) to reduce preoperative anxiety in patients undergoing carotid artery stenting (CAS). Methods A total of 114 patients aged 18–86 years who were scheduled to undergo CAS were randomized to the VR and control groups. Patients in the VR group used a VR headset to view a 16-min psychological intervention video, while those in the control group used a tablet for viewing. The primary assessment instrument was the State Anxiety Inventory (S-AI), which was given 20 min before and after the intervention and 24 h after surgery. Secondary assessment tools were the Self-efficacy for Managing Chronic Disease (SEMCD-6) scale, which was completed before the intervention and 24 h after the operation, a smart bracelet to assess sleep quality, monitored in the evening before the operation, and the VR Suitability and Satisfaction Questionnaire, completed 24 h after the operation. Results The two groups were similar in terms of demographic information, preintervention STAI scores and preintervention SEMCD-6 scores (p > 0.05). S-AI scores were lower in both groups after the intervention and surgery, and the scores of the VR group were lower than those of the control group (p = 0.036, p = 0.014). SEMCD-6 scores post-surgery had improved in both groups, but the VR group had significantly higher scores than the control group (p = 0.005). Smart bracelet measurements showed no significant differences in postintervention sleep quality between the two groups (p = 0.540). For satisfaction, the VR group scored higher in all aspects except scheduling. A total of 47 (85.45%) patients reported having a comfortable experience, and only 5 (9.09%) experienced mild adverse effects. Conclusion The use of a virtual reality psychological intervention was beneficial to reduce the anxiety of patients before CAS and improved their self-efficacy. As virtual reality devices evolve and demonstrate better comfort and safety, more comprehensive and in-depth research of the use of VR to reduce patient anxiety should be performed in the future. Clinical trial registration:https://www.chictr.org.cn/showproj.aspx?proj=186412, identifier ChiCTR2200066219.